2016
DOI: 10.1016/j.jtcvs.2016.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of sternal wound infections

Abstract: Although the incidence of sternal wound infections has decreased to 1% to 4% of all cardiac surgery procedures, they continue to be associated with increased morbidity and mortality, and decreased long-term life expectancy. [1][2][3] They prolong hospital length of stay and can raise hospital costs by as much as US$62,000. 4 Sternal wound infections are now publicly reported, and the US Center for Medicare and Medicaid services will no longer reimburse hospital costs incurred in the treatment of deep sternal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(244 citation statements)
references
References 99 publications
3
234
1
6
Order By: Relevance
“…HP may offer advantages in achieving hemostasis with reduced complications on the sternal bone compared to bone wax. The American Association of Thoracic Surgery has a Class III recommendation against the use of bone wax as it may impair bacterial clearance and bone union, and it presents an independent risk factor for sternal dehiscence . For the HP arm of the study, there was only one AE of sternal dehiscence (1 of 83 cardiothoracic patients [1.2%]) which was not attributed to the use of HP by the investigator and the CEC.…”
Section: Discussionmentioning
confidence: 99%
“…HP may offer advantages in achieving hemostasis with reduced complications on the sternal bone compared to bone wax. The American Association of Thoracic Surgery has a Class III recommendation against the use of bone wax as it may impair bacterial clearance and bone union, and it presents an independent risk factor for sternal dehiscence . For the HP arm of the study, there was only one AE of sternal dehiscence (1 of 83 cardiothoracic patients [1.2%]) which was not attributed to the use of HP by the investigator and the CEC.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of DSWI, it is thought that debridement was the most effective treatment after a timely diagnosis, and the use of antibiotics targeting the pathogenic bacterium was better than dilute povidoneiodine irrigation for the treatment of DSWI (23,27). Some studies have reported that an antibiotic-collagen sponge was effective for the prevention of DSWI.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐operative optimization of nutritional status in patients undergoing cardiac surgery is therefore paramount. The AATS consensus guideline recommends that surgery should be postponed for patients with pre‐operative hypoalbuminemia to receive nutritional nutrition for 7‐10 days if the procedure can be safely delayed . It should be given through the enteral instead of parenteral route, to avoid potential infections and metabolic complications (Class I Recommendation) .…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances in the perioperative care and infection control practices, deep sternal wound infection (DSWI) or mediastinitis continues to have a considerable impact on not only mortality and morbidity but also length of hospital stay and associated health care expenses. In response to these detrimental effects of DSWI, the American Association for Thoracic Surgery (AATS) has recently published expert consenus review guidelines for the prevention and treatment of sternal wound infections in cardiac surgery . This review will discuss the incidence and risk factors of DSWI in the modern era, and associated morbidity and mortality of this complication.…”
Section: Introductionmentioning
confidence: 99%